2016
DOI: 10.1007/s00414-016-1345-0
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography evaluation of the iliac crest apophysis: age estimation in living individuals

Abstract: Determination of the ossification properties of the iliac apophysis is important not only in the clinical evaluation of patients undergoing orthopedic surgery but also in age estimation studies for forensic purposes. The literature includes both anthropological and radiological (conventional radiography, ultrasonography, and magnetic resonance imaging modalities) investigations of the different staging systems used for these purposes. In this study, we assessed the utility of computed tomography (CT) of the il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, the minimum age at the left side of the pelvis for girls and boys was 18 years and 17 years, respectively. [5] These results are in good agreement with those of the present study. This study showed that the determination of bone age with Kreinter's criteria is possible in girls up to the age of 18–20 years.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the minimum age at the left side of the pelvis for girls and boys was 18 years and 17 years, respectively. [5] These results are in good agreement with those of the present study. This study showed that the determination of bone age with Kreinter's criteria is possible in girls up to the age of 18–20 years.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible to investigate the details of apophysis through tomography by evaluating the clavicle ossification. [56789] According to the Study Group on Forensic Age Diagnostics (AGFAD), the radiological evaluation of the left hand, teeth, or clavicle is used to determine the actual age, provided that hand ossification is complete[135101112]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it will be a waste of money and time. There are many reported methods that used bones for age estimation and they are subdivided into three main categories: image processing [29][30][31], by comparing with bone age atlas [32][33][34], and statistical regression analysis [35][36][37][38]. As being compared with the atlas, as the name proposes, X-ray image of the subjects are being made comparison with an atlas which contains a set of radiographs of identified gender and age.…”
Section: Results and Analysismentioning
confidence: 99%
“…Ossification of the iliac crest apophysis has been also used for a long time by forensic experts and anthropologists, who use different staging methods, to determine the age of a person based on direct analysis or X-ray evaluation (13,14) . Iliac crest apophysis has been evaluated with X-rays (15)(16)(17) , ultrasonography (USG) (18)(19) , magnetic resonance imaging (MRI) (18) , and computed tomography (CT) (20) to determine the age, and thus the legal and civil responsibilities, of living individuals, and to verify that athletes have the appropriate licenses.…”
Section: Introductionmentioning
confidence: 99%